2010
DOI: 10.1177/2040620710387981
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment of chronic myeloid leukaemia

Abstract: Since the introduction of imatinib just over a decade ago, there has been a dramatic change in the treatment and prognosis of early chronic phase chronic myeloid leukaemia (CML). This review article focuses on recent advances, culminating in the approval of nilotinib by the US Food and Drug Administration for the treatment of adult patients with newly diagnosed CML in the chronic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Many studies have already been conducted on the combination of TKIs with conventional therapies, including chemotherapy, radiation therapy, interferon therapy, etc. A study showed that combination of standard-dose imatinib and IF-therapy yielded better results than standard-dose or high-dose imatinib alone, as well as standard-dose imatinib combined with chemotherapy [21,163]. Icotinib, an EGFR-TKI is proved to improve radiosensitivity in lung cancer in vitro and in vivo, thus possibly allowing better radiotherapy effects [164].…”
Section: Combination Therapymentioning
confidence: 99%
“…Many studies have already been conducted on the combination of TKIs with conventional therapies, including chemotherapy, radiation therapy, interferon therapy, etc. A study showed that combination of standard-dose imatinib and IF-therapy yielded better results than standard-dose or high-dose imatinib alone, as well as standard-dose imatinib combined with chemotherapy [21,163]. Icotinib, an EGFR-TKI is proved to improve radiosensitivity in lung cancer in vitro and in vivo, thus possibly allowing better radiotherapy effects [164].…”
Section: Combination Therapymentioning
confidence: 99%